Penas e Guitarras Sombrias: Interdisciplinaridade e Estudos Culturais entre Edgar Allan Poe e The Cure as influências da literatura e da música para a subcultura gótica - LARISSA EZIDIO DA SILVA (2024)
The present work aims to carry out an analysis of gothic identities and their cultural manifestations from the perspective of questions about cultural identities and mediations, having as fundamental support the references established by the gothic subculture, considering the artistic and literary production of the writer Edgar Allan Poe (1809-1849) and the artistic and musical production of the band The Cure. The aim is to carry out a discussion based on the influence of Gothic romanticism, which emerged at the end of the 18th century and was evident both in the work of Edgar Allan and in the aesthetics and audiovisual production of the band The Cure. The purpose of this study is to observe the construction of identities, which are incorporated into multiple cultural manifestations, mainly within the Gothic universe. The research will have as its fundamental support the discussions proposed by Cultural Studies, mainly through studies by authors such as Douglas Kellner (2001), Stuart Hall (2006), Nestor García Canclini (1997), Henrique Kipper (2008), among others. Keywords: Edgar Allan Poe; The Cure; Identities; Media; Gothic subculture.